Pendidikan Kesehatan Tentang Kanker Serviks dan Payudara Serta Pemeriksaan Iva Dan Sadari Pada Wanita Usia Subur: Education About Cervic And Breast Cancer as Well as Iva and Breast Examination in Women of Reproductive Age - Astuti, Haryati; Sari, Mia Rita; Madinah, Madinah; Murni, Dahlia (J.Abdimas: Community Health, 2024)
The cancers that have the highest contribution to Indonesian women are cervical and breast cancer. Cervical cancer is in second place and breast cancer is in third place. It is known that nationally the behavior of women of childbearing age is still low in carrying out VIA and BSE examinations. From the data it was found that only 8.3% of women aged 30-50 years carried out early examinations for cervical cancer using the Acetic Acid Visual Inspection method (IVA test) and breast cancer using Self-Examine Your Breasts (BSE). The aim of this activity is that after providing outreach regarding cervical and breast cancer health education, there will be an increase in knowledge of women of childbearing age and increase awareness of checking and detecting cervical and breast cancer early. The method used is providing health education information with counseling to increase knowledge of women of childbearing age about cervical and breast cancer as well as VIA and BSE examinations through lectures, giving leaflets, discussions and questions and answers then carrying out examination simulations followed by direct examination of women of childbearing age with The hope is that awareness will arise of the importance of early detection in order to increase the recovery rate and higher life expectancy as well as improve the level of health in Indonesia.